Peran Communicative Language Teaching dalam Mengembangkan Keterampilan Komunikasi Bahasa Inggris Staf Hotel: Pendekatan Berbasis Praktik - Agung Farid Agustian; R. Vindy Melliany Puspa; Nike Puspita Wanodyatama; Dwijayanti (Forum Komunikasi Dosen, 2025)
This study aims to explore the role of Communicative Language Teaching (CLT) in improving the English communication skills of hotel staff, particularly in the context of hospitality services that require effective and professional interaction with international guests. Using practice-based training methods such as role play, simulation, and task-based learning, this study assesses the effectiveness of a contextual approach to mastering linguistic skills (listening, conversation, vocabulary, and functional speaking), as well as its influence on affective aspects such as confidence, cultural sensitivity, and communication professionalism. Using a one-group pretest-post-test design, 22 hotel staff in Lembang participated in intensive training and were tested before and after the training. The results of the analysis showed significant improvements in all aspects measured. The average participant score rose from 48% (low category) to 74% (fair category), with the greatest improvement occurring in the functional speaking aspect. In addition, field observations revealed that active participation in the training increased participants' courage to speak, fostered sensitivity to guest cultural differences, and shaped a professional attitude in delivering services. These findings confirm that a CLT approach contextualized to real work needs can be an effective and relevant training strategy in the hospitality industry. This training not only improves functional English skills but also equips staff with the interpersonal skills necessary in a multicultural work environment.